Analisis Perspektif Multi-Stakeholder Terkait Pengembangan Taman Kehati Hutan Pelawan dengan Konsep Healing Forest Sebagai Inovasi Pariwisata Berkelanjutan - Dwi Rizky Cahyani; Rahman, Rahman; Ega Apridian; Arian Syahri; Dwi Rizka Zulkia (Lembaga Pengembangan Kinerja Dosen, 2026)
Sustainable tourism has become a key direction of global tourism development, emphasizing the balance between economic, social, and environmental aspects. One of the emerging innovative approaches is the healing forest concept, which utilizes forest environments as natural spaces for physical and mental restoration. This study aims to analyze the perspectives of multiple stakeholders regarding the development of the Taman Kehati Hutan Pelawan in Namang Village, Central Bangka Regency, by implementing the healing forest concept as an innovation for sustainable tourism. The research employed a mixed-method approach (qualitative and quantitative), collecting data through interviews, observations, and questionnaires involving 45 respondents from government institutions, tourism managers, local communities, visitors, academics, and media representatives. Data were analyzed descriptively using Likert scales and qualitative data reduction. The results reveal that both the community and visitors have a positive perception of the area’s development, with the highest scores found in indicators of tourist interest in the healing forest concept (4.48) and support for its development (4.08). Stakeholder perspectives highlight the need for improving human resource capacity, enhancing tourism facilities, and strengthening cross-sector collaboration to achieve sustainable tourism governance.